MODERN LAW IN THE AGE OF SOCIAL CHANGE - Сопілко, Ірина Миколаївна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: the purpose of the scientific article is to summarize the results of the XI International Scientific and Practical Conference «Modern Law in the Age of Social Change» and to develop proposals for intensifying research aimed at solving specific problems in various areas of law that need urgent solution. To achieve a certain goal, general and special scientific (special) methods were used. Use these methods to analyze. Results: the expected results of our International Conference are a scientific substantiation of theoretical and practical aspects of legal reform in Ukraine; solving problems of social standards and outlining the prospects for their implementation in public administration; clarification of criminal policy to combat crime in modern society; determining the impact of social change on the formation of modern civil science, making proposals for development in the context of globalization challenges, economic, air and space law, etc. The interest of a large number of Ukrainian and foreign scientists and legal practitioners in this issue testifies to its relevance and the ability of the scientific community to respond to the challenges of the modern world and actively participate in the social changes taking place today not only in Ukraine but around the world. Discussion: carrying out legal reform in Ukraine is one of the key requirements insisted on by both the Ukrainian expert community and Ukraine’s international partners. The position on the necessity and urgency of changes in the judiciary is shared by Ukrainian society. Undoubtedly, the main task of judicial reform is to establish a fair court and improve the domestic judicial system. The issue of judicial reform and improving the efficiency of justice has always been and remains relevant among scholars. As a result of the study, appropriate proposals and recommendations were made, in particular: take into account the experience of the world’s leading countries in reforming the judicial system of Ukraine on the basis of respect for human rights and fundamental freedoms as a defining foundation in the activities of the judiciary and the judiciary; continue judicial reform, taking into account the need to address the following issues that need to be addressed immediately, in particular the low level of trust in the judiciary, primarily due to corrupt connections, bad behavior of many judges, their dependence and bail; access to justice; failure of the purge policy and change of the judiciary; inefficient access to justice due to violated personnel policy in the courts, high workload on the judiciary and the prevalence of litigation; special attention should be paid to the problem of ensuring the stability of the constitution and a high level of respect for the Basic Law, especially by state bodies and political forces; introduce an effective mechanism for resolving disputes over information disseminated on social networks, as currently national courts in most cases refuse to satisfy claims and do not recognize the relevant information as unreliable and do not oblige defendants to refute it; develop and implement an effective legal mechanism of short-term and long-term comprehensive strategy to overcome poverty in order to improve the quality of life and provide vulnerable groups to the level of minimum standards, including the subsistence level that meets social needs in modern conditions; to continue to expand the practice of interaction of educational institutions with business entities, state and law enforcement agencies, to build a flexible educational process so as to provide an opportunity to introduce new disciplines at the request of the legal services market, at the request of specific employers to train specialists.